Pilot randomised controlled trial of focused narrative intervention for moderate to severe depression in palliative care patients: DISCERN trial. (January 2018) - Lloyd-Williams, Mari; Shiels, Christopher; Ellis, Jacqueline; Abba, Katharine; Gaynor, Edward; Wilson, Kenneth; Dowrick, Christopher
Background: Depression is poorly detected and sub-optimally managed in palliative care patients, and few trials of psychosocial interventions have been carried out in this group of patients. Aims: A pilot trial to determine the effect of a focused narrative intervention on depression in palliative care patients when used in addition to usual care. Design: Patients scoring 10 or higher on Patient Health Questionnaire-9 randomised to focused narrative intervention in addition to usual care or usual care only and followed up at 2, 4 and 6 weeks. A reduction of five points on Patient Health Questionnaire-9 was regarded as clinically significant response to treatment. Setting/participants: Palliative care patients aged over 18 recruited from hospice day care services – exclusion criteria included an estimated prognosis of 6 weeks or less, cognitive impairment and unable to understand written or spoken English. Results: Out of 57 participating patients (71% female), with mean age 65.1 years (range 36–88 years), 33 patients were randomised to the intervention and 24 to usual care only. Mean Patient Health Questionnaire-9 score at baseline was 16.4. Patients receiving intervention had greater reduction in Patient Health Questionnaire-9 score at 6-week follow-up ( p  = 0.04). Median survival was 157 days for intervention and 102 days for control group patients ( p  = 0.07). Conclusion: This pilot trial suggests a focused narrative intervention in palliative care patients with moderate to severe depression can reduce depression scores more than usual care alone. Patients receiving intervention appeared to have longer survival. These results support the need for a fully powered trial.